Inovasi Game Bisik Berantai Berbasis Media Daring sebagai Strategi Pembelajaran Kemahiran Menyimak Bahasa Arab - Hidayati, Triyanti Nurul; Farhah, Eva; Arumi, Afnan; Sukmana, Reza; M. Yunus A (Shaut al Arabiyyah, 2025)
The current technological developments, which are all online, require innovations in the teaching methods for the Arabic language, especially listening skills (maha>ratul-istima’), which are usually conducted offline in the classroom or language laboratory by directly listening to the pronunciation from the lecturer or native speaker via recording or video, then imitating and writing down the transcription results. Considering the current technological developments that cover all aspects, including education and teaching, there is a need for innovations in the teaching methods for language skills, especially listening skills, which, first in the form of face-to-face (offline) practice, became online practice. This research aims to provide alternative teaching in the form of innovations in learning Arabic, especially listening skills, for students through online media-based gaming strategies. This research is qualitative experimentation. Data collection was conducted using three methods: (1) collecting scores using documentation, (2) conducting the gaming process using observation, and (3) obtaining student feedback using interviews. Fifty-eight participants in the game were divided into two classes, namely Class A and Class B. There were 29 people in each class. Each class was divided into five groups, with 5-6 members per group. The game is divided into four scenarios, namely (1) word groups, (2) sentence groups, (3) paragraphs, and (4) character instructions. The game is played entirely online through Zoom Meeting. In this study, five indicators were used to assess listening skills: (1) ability to recognize letters in words (IHK), (2) ability to distinguish similar letter sounds (BBH), (3) understanding sentences (PK), (4) understanding paragraphs (PW), (5) understanding the meaning of vocabulary, phrases, sentences, and discourses (PAK). From the chain whispering game, the average scores per indicator were obtained as follows: CPI (72.8), BBH (72.5), PK (75.2), PW (72.5), and PAK (68). Based on these results, it can be concluded that this online-based chain whispering game can directly train listening skills and, due to the feedback received, is an interactive, memorable, and entertaining form of learning for the students. Keywords: Listening Skill, game, online, Online-Chain Whispers